2022
DOI: 10.3390/diagnostics12092057
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fatigue Syndrome in Patients with Deteriorated Iron Metabolism

Abstract: Fatigue is a common, non-specific symptom that often impairs patients’ quality of life. Even though fatigue may be the first symptom of many serious diseases, it is often underestimated due to its non-specific nature. Iron metabolism disorders are a prominent example of conditions where fatigue is a leading symptom. Whether it is an iron deficiency or overload, tiredness is one of the most common features. Despite significant progress in diagnosing and treating iron pathologies, the approach to chronic fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Due to iron’s toxic properties, the iron level must be strictly regulated in the human body. The regulation of the body’s iron concentration at the systemic level is complex and is based on the activity of the peptide hormone hepcidin and protein transferrin (Tf) [ 71 , 72 ]. Initially, iron is absorbed from the duodenum and small intestine into enterocytes and macrophages, which combine with apoferritin to form ferritin.…”
Section: Systemic and Cell Regulation Of Iron Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to iron’s toxic properties, the iron level must be strictly regulated in the human body. The regulation of the body’s iron concentration at the systemic level is complex and is based on the activity of the peptide hormone hepcidin and protein transferrin (Tf) [ 71 , 72 ]. Initially, iron is absorbed from the duodenum and small intestine into enterocytes and macrophages, which combine with apoferritin to form ferritin.…”
Section: Systemic and Cell Regulation Of Iron Metabolismmentioning
confidence: 99%
“…Hereditary hemochromatosis (HH) is one of the most common inherited metabolic diseases and it is associated with an 80% mutation of the HFE gene at position C282Y [ 71 , 72 ]. It leads to impaired iron metabolism through the increased absorption of this micronutrient from the gastrointestinal tract and its abnormal distribution.…”
Section: Iron Metabolism Disorders As the Trigger Of Oxidative Stressmentioning
confidence: 99%
“…Iron deficiency is a prevailing cause of nutritional deficiency 1 . The Global Burden of Disease Study 2021 reported that IDA is the leading cause of anemia, accounting for 66.2% of all anemia cases.…”
Section: Introductionmentioning
confidence: 99%
“…Iron is a micronutrient essential for the binding and transport of oxygen, the storage of iron, and the regulation of cellular respiration. Iron is an essential constituent of mitochondrial enzymes and myoglobin; thus, iron deficiency may result in fatigue and weakness before hemoglobin levels decrease 1 .…”
Section: Introductionmentioning
confidence: 99%